2021
DOI: 10.1177/01430343211039266
|View full text |Cite
|
Sign up to set email alerts
|

From early to late adolescence: Effect of problematic mobile phone use on depression of adolescents

Abstract: Problematic mobile phone use can predict depression in adolescents, but few studies have thoroughly explored its internal mechanism. This study surveyed 1,768 Chinese adolescents in three educational levels (upper grades of elementary, junior middle, and high school levels) using a questionnaire. Results showed that (1) problematic mobile phone use significantly positively predicted adolescents’ depression after controlling for gender and age, (2) parent–child relationship played a mediating role between probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…On the other hand, positive coping strategies are needed to adopt for reducing students' PMPU. The study found that students with psychological symptoms such as anxiety, depression and stress were more likely to get PMPU, while students with mild psychological symptoms were less likely to get PMPU (Augner and Hacker, 2012;Zou et al, 2019;Kong et al, 2021). Therefore, schools can regularly screen students with mental problems and provide professional mental health services for them (Liu R. D. et al, 2019;Ohrt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, positive coping strategies are needed to adopt for reducing students' PMPU. The study found that students with psychological symptoms such as anxiety, depression and stress were more likely to get PMPU, while students with mild psychological symptoms were less likely to get PMPU (Augner and Hacker, 2012;Zou et al, 2019;Kong et al, 2021). Therefore, schools can regularly screen students with mental problems and provide professional mental health services for them (Liu R. D. et al, 2019;Ohrt et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on attachment theory, a good parent-child relationship can provide children with warmth and social support [24]. Additionally, it was found that positive parent-child relationships could reduce adolescent depressive symptoms [25], but conflicts between parents and children (a poor parentchild relationship) are positively associated with children's depressive symptoms [26]. Thus, parental phubbing may precipitate adolescent depressive symptoms by deteriorating the parent-child relationship.…”
Section: Parental Phubbing Parent-child Relationship and Depressive S...mentioning
confidence: 99%
“…In the context of adolescents, Zhang et al (2023) found a positive correlation between teenage phubbing and conflicts with parents. Moreover, parental phubbing was related to depression in students of different educational levels in China ( Kong et al, 2021 ; Hu et al, 2023 ; Mi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%